2018
DOI: 10.1016/j.hrthm.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Sleep characteristics that predict atrial fibrillation

Abstract: Sleep disruption consistently predicted AF before and after adjustment for OSA and other potential confounders across several different populations. Sleep quality itself may be important in the pathogenesis of AF, potentially representing a novel target for prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 32 publications
(39 reference statements)
4
42
0
2
Order By: Relevance
“…Yet , it is possible that differences in HF or comorbidity between CBT-I and attention-control groups or unmeasured differences in HF contributed to our findings.. Other HF and cardiovascular characteristics (e.g., dysrhythmias) should be considered in more detail in future studies. For example, recent evidence suggest that atrial fibrillation contributes to insomnia (Chokesuwattanaskul et al, 2018;Christensen et al, 2018;Han et al, 2017;Lee et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Yet , it is possible that differences in HF or comorbidity between CBT-I and attention-control groups or unmeasured differences in HF contributed to our findings.. Other HF and cardiovascular characteristics (e.g., dysrhythmias) should be considered in more detail in future studies. For example, recent evidence suggest that atrial fibrillation contributes to insomnia (Chokesuwattanaskul et al, 2018;Christensen et al, 2018;Han et al, 2017;Lee et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A recent observational study showed that lack of rapid eye movement sleep is associated with an increased risk of incident AF [26]. Both subjectively reported sleep difficulty and objectively assessed short sleep duration have been linked to AF [26,27]. These findings highlight the complex interplay between sleep in its entirety and AF [20].…”
Section: Sleep Apnea and Atrial Fibrillationmentioning
confidence: 97%
“…Lack of deep sleep was found to be more common in patients with AF independent of OSA [24,25]. A recent observational study showed that lack of rapid eye movement sleep is associated with an increased risk of incident AF [26]. Both subjectively reported sleep difficulty and objectively assessed short sleep duration have been linked to AF [26,27].…”
Section: Sleep Apnea and Atrial Fibrillationmentioning
confidence: 99%
“…Initially informed by the observation that self-report of frequent nighttime awakening was associated with prevalent AF in the Health eHeart Study, we subsequently showed that a similar self-report of nighttime awakening predicted incident AF in the Cardiovascular Health Study. 5 In both cases, relationships persisted after adjusting for conventional AF risk factors, including available evidence of OSA. We then analyzed 1,127 Cardiovascular Health Study participants in the subcohort of the Sleep Heart Health Study and found that decreased rapid eye movement (REM) sleep was significantly predictive of incident AF after adjusting for potential confounders, including polysomnogram-based OSA indices collected concurrently.…”
mentioning
confidence: 92%